Social representation underlying the paradigmatic discourse of the novice tutors and master’s experts of the Liberating Experimental Pedagogical University (Revista Electrónica REDINE, 2024)
The study is a field research of qualitative nature, oriented under the interpretive paradigm and with the phenomenological-hermeneutic approach. Its intention has been to unveil, interpret, understand and generate the social representation underlying the paradigmatic discourse of the novice tutors and masters experts of UPEL-IPB. The theoretical sampling is intentional, since the opinion of the social actors is heard.  The participant observation and interview allowed to collect the necessary information to visualize a broad picture of the phenomenon. They also provided inputs for the production of knowledge; it is important to note that the script made it easier for social actors to report their opinions and anecdotes. The same, went through a process of categorization that was then triangulated with the different authors and with the intellectual capital that the researcher has with respect to paradigmatic discourse. The following categories emerged from the interpretation: academic prestige in the discursive community, academic-discursive affinities. Linguistic and Communicative Competence of the Tutor, Towards the Coherent Production of the Paradigmatic Discourse, Protagonism Tutorial in the Production of the Paradigmatic Discourse, A Distinction to the Paradigmatic Primacy, A Toolbox for Discursive Construction and a Square Table for Knowledge Production. The reflections confirm that the social representation underlying discourse is on the path of generating knowledge through speech, own experience and others, the truth is that it is in the task of searching for the truth of each discursive orientation and that they are multiple, each with a specific form and background with the paradigm, In other words, discourse is built on the basis of theory and its applicability to the reality of each social actor.
Keywords: Social representation; Paradigmatic discourse; discursive community; Tutor